2003
DOI: 10.2308/aud.2003.22.1.69
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting the Choice to Participate in Flexible Work Arrangements

Abstract: Assurance services firms have attempted to mitigate turnover and personnel shortages by offering flexible work arrangements (FWAs) to their professional staff. Little is known however, about what factors affect whether these professionals choose to adopt a FWA. This study examines factors potentially associated with both intentions to adopt and ultimate adoption of a FWA for a sample of seniors, managers, and partners at two national and one regional assurance services firms. Results indicate that intentions t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
51
1
10

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(71 citation statements)
references
References 18 publications
9
51
1
10
Order By: Relevance
“…Thompson, Beauvais, & Lyness (1999) found that employees will only utilize work-family benefits when the organization has a culture that is supportive of their utilization. The results of Almer, Cohen, & Single (2003) support this finding, and also indicate that the intention to utilize flexible work arrangements is based upon both organizational and personal considerations. Thus, despite the availability of flexible work arrangements in public accounting, it is quite possible that employee expectations with respect to their ability to achieve work-family balance may not be met if the accounting firm's culture does not support their use.…”
Section: The Role Of Employee Expectationssupporting
confidence: 75%
“…Thompson, Beauvais, & Lyness (1999) found that employees will only utilize work-family benefits when the organization has a culture that is supportive of their utilization. The results of Almer, Cohen, & Single (2003) support this finding, and also indicate that the intention to utilize flexible work arrangements is based upon both organizational and personal considerations. Thus, despite the availability of flexible work arrangements in public accounting, it is quite possible that employee expectations with respect to their ability to achieve work-family balance may not be met if the accounting firm's culture does not support their use.…”
Section: The Role Of Employee Expectationssupporting
confidence: 75%
“…This finding follows in general the outcomes of Giannikis andMikhail (2011), McNamara et al (2012) and Almer et al (2003), which all suggest that employees would be more likely to start using flexible working options if doing so contributes to achieving the desired work-life balance without hindering relationships with colleagues. Another explanation could be however that those working from distance are out of sight of their colleagues and can thus decide more freely about the start and end times of their working day, which in turn facilitates their creativity.…”
Section: Discussionsupporting
confidence: 55%
“…Giannikis and Mikhail (2011) propose that employees are more likely to opt for a flexible working time option if it helps them achieve the work-life balance they desire, while the probability decreases if employees recognise there will be a negative impact on their career progress, relationships with colleagues and compensation. McNamara et al (2012) also find that the perceived negative effect on career progress is the main reason employees do not opt for flexible working time, whereas Almer et al (2003) conclude that the attitude of colleagues is an important factor when people consider whether to opt for a flexible working arrangement.…”
Section: Literature Reviewmentioning
confidence: 96%
“…This study was conducted in the Klang Valley, the central business hub of Malaysia, using a quantitative method adapted from [22]. Based on the statistics from the Labour Force Survey Report Malaysia, 2011, six sub-groups in the services sector which had a substantial number of working women were identified.…”
Section: Introductionmentioning
confidence: 99%